1966
DOI: 10.1111/j.1570-7458.1966.tb02357.x
|View full text |Cite
|
Sign up to set email alerts
|

ÜBER DEN SITZ DER CO2‐REZEPTOREN BEI DER LARVE VON OTIORRHYNCHUS SULCATUS

Abstract: Mit Hilfe bilateraler Exstirpation der Kopfanhänge der Larve von O. sulcatus wurde der Sitz der Chemorezeptoren lokalisiert, welche bei der Orientierung im CO2‐Gradienten beteiligt sind. Diese CO2‐Rezeptoren liegen hauptsächlich auf den Endgliedern der Maxillarpalpen, wahrscheinlich auf deren Spitze. Fühler und Labialpalpen sind an der Orientierung nur in sehr geringem Masse beteiligt, die letzteren möglicherweise gar nicht. Unilaterale Exstirpation aller drei Kopfanhänge führte zu Wendungen nach der intakten … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1974
1974
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…In these species digitiforni sensilla have been found on the distal segment of the maxillar palp (Honomichl 1980 and unpublished results). The papers of Doane and Klingler (1978), Klingler (1966), and White et al (1974) give a remarkable hint in another direction. The authors describe the loci of C02-reception in several larval Coleoptera and they find that the maxillar palps possess a greater number of C02-receptors than the labial palps.…”
Section: Discussionmentioning
confidence: 99%
“…In these species digitiforni sensilla have been found on the distal segment of the maxillar palp (Honomichl 1980 and unpublished results). The papers of Doane and Klingler (1978), Klingler (1966), and White et al (1974) give a remarkable hint in another direction. The authors describe the loci of C02-reception in several larval Coleoptera and they find that the maxillar palps possess a greater number of C02-receptors than the labial palps.…”
Section: Discussionmentioning
confidence: 99%
“…Klingler (1966) conducted amputation experiments on the antennae and on the maxillary and labial palps in order to identify the location of the sensory organs that mediate this capacity. He concluded that the CO 2 -receptor neurons are predominantly located on the maxillary palps, in particular the terminal segment, but that there is also a measurable but weak influence of the antennae on orientation performance.…”
Section: Coleoptera: Larval Head Appendagesmentioning
confidence: 99%
“…In contrast to work aimed at identifying specific plant chemicals responsible for host location, Klinger (56,57), identified carbon dioxide as an important nonspecific chemical influencing soil insect host-finding in several cases. Many soil insects (24, 36,44,52,56,57,76,90,96) are attracted to carbon dioxide.…”
Section: Host Findingmentioning
confidence: 99%
“…Many soil insects (24, 36,44,52,56,57,76,90,96) are attracted to carbon dioxide. Carbon dioxide is released by decaying organic matter in the soil as well as by living plant roots.…”
Section: Host Findingmentioning
confidence: 99%